Upbringing into sustainable development in the context of Catholic Social Science - Grochowska, Irena (Studia Ecologiae et Bioethicae, 2009)
One of the basic calls of the modern church is to call secular people to engage in the process of evangelization and building the new humanism. In 1947 Pius XII announced the apostolic constitution Provida mater Ecclesia giving in this way theological and legal form to such experience as secular institutions. In modern days the call is clearer, because it directs the invitation to all of us, to participate in building church unity recognizing only one’s vocation in the world. The biggest concern of the church is not an answer to moral responsibilities (what one should do or not), not about natural laws or sociological analyses, political or anthropological, or ethical and ideological confusion, which are the domain of the modern world, but the axis of the church is the concern, for the power coming from Christ’s cross being wasted. Catholic Social Science does not ignore philosophy, law, and science as such, but the basis of its science is Christ. The essence of realization of the Catholic Social Science program is to get acquainted with the science, upbringing in its spirit, and using it throughout activities in various social environments. Man today should realize how useful engagement and responsibility for the natural environment are. The modern church participates in the concern about the environment. In John Paul II's teachings, we could find a call to action in favor of it. Benedict XVI as one of the most important tasks of our times acknowledged the idea of balanced development.